Prevalence of uropathogen producing extended spectrum beta lactamase (ESBL) at urinary tract infection in chronic kidney disease patients - Wijaya, Carolin; Eriata, Anselmus Helbert; Rustawan, I Nengah Tony; Candra, I Kadek Bayu Adhi; Budayanti, Ni Nyoman Sri (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2023)
Background: Urinary tract infection (UTI) is one of the most common bacterial infections encountered by clinicians in developing countries. UTI in patients with Chronic Kidney Disease (CKD) caused by ESBL-producing gram-negative bacteria has been increased in different countries. The common uropathogenic Gram negative bacteria are Escherichia coli and Klebsiella pneumoniae. The aim of this study was to identify prevalence of the common uropathogen producing ESBL E. coli and K. pneumonia among the patients with urinary tract infection (UTI) in chronic kidney disease as well as the susceptibility of antibiotic therapy. Methods: This was a cross-sectional retrospective study to evaluate clinical urine isolates collected from Prof. Dr. I.G.N.G. Ngoerah Hospital within July 2019 until July 2020. Identification and susceptibility tests in urine isolate were performed by Vitex-2 System (Biomerieux) and interpreted with CLSI 2020 standard. Results: From 1291 urine specimens, 210 urine specimens were collected (29.43%) from patients with UTI in CKD during 12 months. Prevalence of uropathogen in chronic kidney disease from urine specimens were E.coli (41.57%), K.pneumoniae (13.15%), and Pseudomonas aeruginosa (7.36%). It was found that ESBL produced E. coli (56.32%) and also K. pneumoniae (54%). Susceptibility antibiotic E. coli and K. pneumonia of UTI patient with CKD with ESBL producers were meropenem (99,10%), amikacin (98,07%), tigecycline (92,30%), gentamicin (80%), and fosfomycin (79,47%). Conclusion: ESBL producers in patient UTI in CKD patients were E. coli 56,32%, K. pneumoniae 54% that were sensitive to meropenem, amikacin, tigecycline gentamicin, fosfomycin.